PENERAPAN PEMBELAJARAN TARI GANTAR UNTUK MENINGKATKAN MOTORIK KASAR ANAK USIA DINI DENGAN MENGGUNAKAN KONSEP Developmentally Appropriate Practice (DAP) DI TK KARTIKA V-66 BALIKPAPANTAHUN PELAJARAN 2014-2015 - Euis Yuniastuti (Jurnal Penelitian Pendidikan)
This research aimed at improving gross motor skills of Group B preschoolers through the learning of Tari Gantar traditional dance at TK Kartika V-66 Balikpapan using the concept of Developmentally Appropriate Practice (DAP) in academic year 2014-2015. This research was designed as classroom action research which was carried out in three learning cycles: (1) action planning; (2) action execution; (3) observation and evaluation and (4) reflection. Researcher acted as dance teacher and researcher’s colleagues took a role as observers. The data was collected by filling in observation sheet, writing field notes, taking documentations and evaluating research activities. Qualitative analysis was equally performed to interpret the improvement of teacher’s and students’ activities in each cycle, while quantitative analysis was performed to explain the improvement of the students’ gross motor skills. Three aspects in gross motor skills measured in the research are locomotor, non-locomotor and manipulative skills. Results of the research exhibit the significant improvement of students’ gross motor skills throughout learning cycles. In cycle 1, the average value of students’ gross motor skills was about 75.13 while the average accomplishment percentage reached only 60.00%. In cycle 2, the average value of students’ gross motor skills increased at 76.31, while the average accomplishment percentage reached 80.00%.In cycle 3, the average value of students’ gross motor skills increased at 77.68while the average accomplishment percentage finally reached 92.00%.Teacher’s activity was significantly improved from cycle 1 at 70.00%, tocycle2at 86.67 % and finally to cycle 3at 100.00%.Finally, students’ activity was significantly improved from cycle 1 at 46.67%, to cycle2at 73.33% and finally to cycle 3 at 86.67%.